Correction: Prevalence of Lymphatic Filariasis and Treatment Effectiveness of Albendazole/ Ivermectin in Individuals with HIV Co-infection in Southwest-Tanzania. - Inge Kroidl; Elmar Saathoff; Lucas Maganga; Petra Clowes; Leonard Maboko; Achim Hoerauf; Williams H Makunde; Antelmo Haule; Prisca Mviombo; Bettina Pitter; Neema Mgeni; Joseph Mabuye; et al. (PLoS Neglected Tropical Diseases, 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004618.].